2020
DOI: 10.33545/27068919.2020.v2.i1a.44
|View full text |Cite
|
Sign up to set email alerts
|

Insurgency, armed banditry and corruption in Nigeria: The bane of socio-economic underdevelopment

Saheed G Adegoke

Abstract: This paper examines the socio-economic effects of insurgency, armed banditry and corruption in Nigeria. The country as a nation state is under a severe internal socio economic and security threat. As a more general level, the threat has social, economic, political and environmental dimensions. Each of these dimensions has greatly affected the nation's stability, and can be traced to the ethnic militia armies, ethnic and religious conflicts, poverty, terrorism, armed robbery, corruption, economic sabotage and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The economic impact of terrorism in nations affects vital industries such as aviation, manufacturing, and tourism and ultimately impacts stock performance (Mwangi, 2017). A study suggested that public officers' corruption, improper sharing of information, and unemployment are the causes of corruption, banditry, kidnappings, and insurgency in Nigeria (Adegoke, 2020). The impact of crime on SMEs is colossal due to the cost incurred due to destruction and damage, anxiety, and fear implicated owners/managers and other stakeholders (Sifuna, 2018).…”
Section: Political Environmentmentioning
confidence: 99%
“…The economic impact of terrorism in nations affects vital industries such as aviation, manufacturing, and tourism and ultimately impacts stock performance (Mwangi, 2017). A study suggested that public officers' corruption, improper sharing of information, and unemployment are the causes of corruption, banditry, kidnappings, and insurgency in Nigeria (Adegoke, 2020). The impact of crime on SMEs is colossal due to the cost incurred due to destruction and damage, anxiety, and fear implicated owners/managers and other stakeholders (Sifuna, 2018).…”
Section: Political Environmentmentioning
confidence: 99%
“…Ameh and Aliyu (2023) link the emergence of banditry crisis in Nigeria to the nation's weak security and intelligence system. Adegoke (2020) laments that the problem of banditry has become a harsh reality in contemporary Nigeria and is manifesting in the form of kidnapping, suicide attacks, selfsuicide bombing, insurgency, armed robbery, among others. Similarly, Ibrahim and Mutawalli (2020) state that banditry in Nigeria has become a major security challenge that is precipitating instability, weakening states and making the environment vulnerable to threats that are obstacles to the achievement of socio-economic development.…”
Section: Literature Reviewmentioning
confidence: 99%